Identification and functional characterization of the MdHB-1 gene promoter sequence from Malus×domestica - Hao-jie WANG; Yong-hua JIANG; Ying-wei QI; Jie-yu DAI; Yan-li LIU; Xian-bo ZHU; Cui-hua LIU; Yan-rong LÜ; Xiao-lin REN (Journal of Integrative Agriculture, 2017)
Abstract: Homeobox 1 in Malus×domestica (MdHB-1) is a transcription factor that belongs to homeodomain-leucine zipper I (HD-Zip I) protein subfamily. According to previous reports, MdHB-1 could regulate ethylene synthesis by binding with the MdACO1 promoter, but other functions of MdHB-1 are still unknown. To reveal more clues concerning the characters of the MdHB-1 gene promoter and the functions of MdHB-1, the promoter region of MdHB-1 was cloned from the Royal Gala apple genome and recombined with the β-glucuronidase (GUS) gene in this study. This research was conducted in Nicotiana tabacum and supported by Agrobacterium-mediated transient transformation and bioinformatics analysis. Deletion analysis of the MdHB-1 promoter showed that the GUS gene could be activated by serially deleted promoters, and the activity promoted by 680 nucleotides (nt) was the lowest. The region, which is 266 nt upstream of the initiation code (ATG), was effective for GUS expression. Meanwhile, the activity of the MdHB-1 promoter (−1 057 nt), which was stronger than MdHB-1 promoter (−1 057 to −266 nt) and lack the 5′-untranslated region (5′-UTR), showed that 5′-UTR may have a positive effect on gene transcription. After the sequence analysis, the cis-acting elements that respond to hormones and environmental stresses were identified in the promoter region. The MdHB-1 promoter (1 057 nt) activity in Nicotiana tabacum was positively induced by ethrel and darkness, and it was suppressed by gibberellic acid (GA), whereas abscisic acid (ABA), salicylic acid (SA), wounding, and Pseudomonas syringae pv. tomato (DC3000) treatments revealed a slight auxo-action. These results reveal that the MdHB-1 promoter receive internal or external signals, and MdHB-1 may refer to many biological activities in apple, such as its stress response, development, and ripening.